2018
DOI: 10.3389/fmed.2018.00092
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Search of the Ideal Cut-Off of the Sysmex UF-1000i® Flow Cytometer for the Diagnosis of Urinary Tract Infection in a Tertiary Hospital in Spain

Abstract: Urinary tract infections (UTI) are one of the most prevalent infections. A rapid and reliable screening method is useful to screen out negative samples. The objective of this study was to validate the Sysmex flow cytometer UF-1000i by evaluating its accuracy, linearity and carry-over; and define an optimal cut-off value to be used in routine practice in our hospital. For the validation of the UF-1000i cytometer, precision, linearity and carry-over were studied in samples with different counts of bacteria, leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
(79 reference statements)
3
7
0
Order By: Relevance
“…Overall performance of automated urinalysis by the UF-1000i, based on AUC values, was better for men compared to women for both leucocyte and bacterial count. The few other studies focusing on genderspecific performance of the UF-1000i reported this as well [17][18][19]. Compared to these studies, our leucocyte AUC values were similar (reported range: men 0.876-0.950, women 0.798-0.937), while our bacterial AUC values were somewhat lower (reported range: men 0.956-0.990, women 0.930-0.946).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Overall performance of automated urinalysis by the UF-1000i, based on AUC values, was better for men compared to women for both leucocyte and bacterial count. The few other studies focusing on genderspecific performance of the UF-1000i reported this as well [17][18][19]. Compared to these studies, our leucocyte AUC values were similar (reported range: men 0.876-0.950, women 0.798-0.937), while our bacterial AUC values were somewhat lower (reported range: men 0.956-0.990, women 0.930-0.946).…”
Section: Discussionsupporting
confidence: 78%
“…In general, our gender-specific leucocyte cut-off values were somewhat higher (men 60/µL, women 43/µL) compared to other studies (men 3.9-52.1/µL, women 3.8-31.5/µL). The bacterial cut-offs (men 75/µL, women 139/µL) were within the reported range (men 31.3-240.5/µL, women 95-689.0/µL) [17][18][19]. It is important to realize that these studies used positive UC as definition of UTI, were not situated in an ED setting, and used different sensitivities to determine the cut-off values.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…According to the reviewed literature, the cut-off values used range from 25 to 230 bacteria/μL (2, 12, 18, 2123). In our study, the best cut-off point was found after comparing the results of culture and bacterial or leukocyte count, and it was 138 bacteria/μL or 119.8 leukocyte/μL (SE 95.3%, SP 70.4%) with the UF-1000i (24). This cut-off value had a similar SE and a higher SP than the cut-off point obtained with the FUS200 (5.7 bacteria/μL or 4.3 leukocyte/μL; 95.8% SE, 44.4% SP) (Table 2).…”
Section: Discussionmentioning
confidence: 71%
“…Flow cytometry analysis is capable of identifying bacteria, and the Sysmex UF-1000i (Sysmex, Kobe, Japan) flow cytometer has been developed to standardize urine analyses [7]. This system can analyze urine particles rapidly, such as white blood cells (WBC), red blood cells (RBC), bacteria, epithelial cells, and casts effectively and reliably.…”
mentioning
confidence: 99%